Keabsahan Akta Jaminan Fidusia Yang Tidak Ditandatangani Dihadapan Notaris dalam perspektif Undang-Undang Jabatan Notaris dan Undang-Undang Jaminan Fidusia - Ketut Septian Dripananda; Lastuti Abubakar; Nanda Annisa Lubis (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This study analyzes the validity of a fiduciary security deed not signed before a notary based on the Notary Position Law and Fiduciary Security Law, and legal protection for harmed parties. The normative juridical method with an analytical descriptive approach was used. Results show a fiduciary security deed not signed before a notary degrades into a private deed, rendering it null and void by law and unable to be registered at the Fiduciary Registration Office. Legal protection for harmed creditors allows claiming compensation, costs, and interest from the notary if proven to violate the Notary Position Law provisions. The study concludes the notary's presence during fiduciary security deed signing is crucial to ensure validity and legal certainty for involved parties. The degraded deed's lack of registration prevents creditors from executing the fiduciary security, emphasizing notarization's importance in protecting creditor interests. Key Words: Degradation; Fiduciary Security Deed; Notary